Perceived Use Behavior of Social Networking Sites Among the Healthcare Students in India - Abu Elnasr E. Sobaih PhD; Abdul Baquee PhD; Ishfaq Ahmad Palla PhD; Shamim Aktar Munshi (SAGE Publishing, 2023)
Introduction The use of social networking sites (SNSs) is growing among higher education students, including healthcare students. Nonetheless, limited research has examined the perceived use behavior among healthcare students in developing countries such as India. Objective This study attempts to assess the use behavior of SNSs by undergraduate students in the fields of nursing and pharmacy in India through the lens of Connectivism and New Social Learning theories. Method The study used a Google form to collect data through an online questionnaire. A sample of 483 participants included 258 Bachelor of Science in Nursing students, 161 General Nursing and Midwifery students, and 64 Bachelor of Pharmacy students from various Indian nursing and pharmacy schools. Results The majority of the respondents prefer to use SNSs for several purposes such as watching academic videos on YouTube, sharing their ideas, thoughts, and current development in their respective fields through WhatsApp, getting job-related information from different Facebook pages, etc. A substantial number of nursing students believed that these SNSs help them build relationships with professionals across the country. At the same time, many students also indicated that extensive use of SNSs might cause sleep difficulties, data privacy concerns, and a lack of focus while studying. Conclusion To have an impact on how SNSs are used in healthcare education, more attention should be paid to build connectivism between educators and their students on social learning environment, which the findings of this study's suggestions could be put into practice.